Airway inflammation in patients with bronchiectasis - Đurđević, Nataša; Milenković, Branislava; Janković, Jelena; Mitić, Javorka; Belić, Slobodan; Jordanova, Elena; Baralic, Marko B (Halo 194 Scientific Journal of Emergency Medicine, 2021)
Bronchiectasis is a chronic lung disease characterized by an abnormal enlargement of the lumen of the bronchi caused by the weakening or destruction of the muscular and elastic components of the bronchial wall, decreased mucus clearance, and to frequent infections of the respiratory tract . The gold standard for the diagnosis of bronchiectasis is high resoluted computed tomography (HRCT) of the thorax . The infection and colonization of the respiratory tract contribute to increasing inflammation and further damage to the lung. Upon entry of pathogens into the respiratory tract by activation of epithelial cells, macrophages and dendritic cells. Inflamation cells secrete chemical mediators and they acctivated immune response and thus allow the phagocytosis of pathogens. Earlly diagnostic, appropriate treatment of and interrupting the vicious circle between infection and infalamacije in patients with bronchiectasis, contribution to prevention of structural changes of the airways.
Keywords: Key words: bronchiectasis, inflamation, infection